2009
DOI: 10.1038/sj.bjc.6604988
|View full text |Cite
|
Sign up to set email alerts
|

Vandetanib (ZD6474), an inhibitor of VEGFR and EGFR signalling, as a novel molecular-targeted therapy against cholangiocarcinoma

Abstract: Cholangiocarcinoma is an intractable cancer, with no effective therapy other than surgical resection. Elevated vascular endothelial growth factor (VEGF) and epidermal growth factor receptor (EGFR) expressions are associated with the progression of cholangiocarcinoma. We therefore examined whether inhibition of VEGFR and EGFR could be a potential therapeutic target for cholangiocarcinoma. Vandetanib (ZD6474, ZACTIMA), a VEGFR-2/EGFR inhibitor, was evaluated. Four human cholangiocarcinoma cell lines were molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 45 publications
4
63
0
1
Order By: Relevance
“…The EGFR signaling pathway is integral in epithelial cell growth and proliferation, where preclinical studies have shown tumor regression with EGFR inhibition (28,30), forming the rationale for targeting EGFR for treatment. While initial small studies demonstrated promising antitumor activity with anti-EGFR therapy in combination with gemcitabine-based chemotherapy (31,32), these findings were unable to translate into a significant clinical benefit in larger randomized clinical trials (33,34 (35,36).…”
Section: Egfr Signaling Pathwaymentioning
confidence: 99%
“…The EGFR signaling pathway is integral in epithelial cell growth and proliferation, where preclinical studies have shown tumor regression with EGFR inhibition (28,30), forming the rationale for targeting EGFR for treatment. While initial small studies demonstrated promising antitumor activity with anti-EGFR therapy in combination with gemcitabine-based chemotherapy (31,32), these findings were unable to translate into a significant clinical benefit in larger randomized clinical trials (33,34 (35,36).…”
Section: Egfr Signaling Pathwaymentioning
confidence: 99%
“…In support of this notion, inhibition of VEGFR and EGFR signaling with vandetanib (ZD6474, a tyrosine kinase inhibitor) can be an important approach for the management of the subset of cholangiocarcinoma that lack KRAS mutations and/or have EGFR amplification (Yoshikawa et al 2009). Furthermore, ZD1839 (IRESSA), an orally active, selective inhibitor of EGFR tyrosine kinase has clinical activity against cholangiocarcinoma by stabilizing the cell cycle inhibitor, p27Kip1 and enhancing radiosensitivity in cholangiocarcinoma cell lines (Yabuuchi et al 2009).…”
Section: Angiogenesis In Cholangiocarcinomamentioning
confidence: 99%
“…The factors that drive angiogenesis have also been shown to have distinct effects on cholangiocyte and cholangiocarcinoma growth in an autocrine manner Tang et al 2006;Mobius et al 2007;Yabuuchi et al 2009;Yoshikawa et al 2009;Glaser et al 2010). Indeed, the proliferative effects of estrogen on cholangiocarcinoma cell lines have been attributed to a mechanism involving the upregulation of VEGF expression, as blocking VEGF ameliorates the estrogenic effects on proliferation (Mancino et al 2009).…”
Section: Angiogenesis In Cholangiocarcinomamentioning
confidence: 99%
“…In an examination conducted using human cholangiocarcinoma cell lines, ZD6474, an inhibitor of VEGFR and EGFR signaling, showed promising anticancer activity [32]. This study revealed that the absence of KRAS mutation and presence of EGFR amplification may be potentially predictive molecular markers of the sensitivity of cholangiocarcinoma to EGFR-targeted therapy [32].…”
Section: Preclinical Studies Of the Molecular Biology Of Biliary Tracmentioning
confidence: 99%